A critical look at partial acceptability in English and Polish - Żychliński, Sylwiusz (Yearbook of the Poznan Linguistic Meeting, 2021)
This paper is primarily concerned with the role of partial acceptability (and its ‘flavors’) in English linguistic examples taken from the field of generative grammar. Partially acceptable judgments as a subset of acceptability judgments form a heterogeneous group that plays a significant role in linguistic research and yet the extent to which partial acceptability is employed in the linguistic literature has not been studied extensively. The first part of the paper discusses a number of relevant issues related to the use of partial acceptability, such as problems with the conceptualization of gradience or excessive creativity with regard to levels of acceptability present in generative papers. The second part of the paper reports on a meta-linguistic study of partial acceptability in a pre-selected corpus of generative papers on English, with the focus on the types of partial acceptability and their function. Lastly, the English results are compared with the results of a previously conducted similar study of partial acceptability in Polish.